UTILIZING DEBATE METHOD IN EFL CLASS TO IMPROVE THE ARGUMENTATIVE WRITING ABILITY OF THE STUDENTS - Halinda Halinda; Hana Sazida; Luthfia Assyifa; Rofifah Humaira; Sheviana Aisyiah; Izzah Supeni (Universitas Sriwijaya, 2022)
Argumentative writing is a crucial part of the language learning process. Nevertheless, many students find writing, especially argumentative, a problematic English skill. Therefore, the researchers want to know the use of the debate method to improve students' argumentative writing ability in Islamic Boarding School. The objective of this research referring to the research problem is to find out the use of the debate method to improve argumentative writing ability. The design of this research is Qualitative and descriptive. The research subject is the ten alumni of modern Islamic Boarding Schools, consisting of 7 women and three men who had learned the debate method in argumentative writing. The data collection techniques used in this study are interviews and documentation. The finding is that improving students' ability to write argumentative paragraphs by applying debate techniques. Students feel facilitated and motivated in the learning process, so students' ability to write argumentative paragraphs increases.